2020
DOI: 10.1099/ijsem.0.004343
|View full text |Cite
|
Sign up to set email alerts
|

Hymenobacter ginkgonis sp. nov., isolated from bark of Ginkgo biloba

Abstract: Strain HMF4947T, isolated from the bark of a ginkgo tree, was a pale-pink coloured, Gram-stain-negative, non-motile, strictly aerobic and rod-shaped bacterium. The isolate grew optimally on Reasoner's 2A agar at 30 °C, pH 7.0 and with 0 % NaCl. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain HMF4947T belonged to the genus Hymenobacter and was most closely related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The pH range for growth was determined (pH 5.0, 6.0, 7.0, 8.0, 9.0, 10.0) and using R2A media adjusted by appropriate buffering agents 0.1 M sodium acetate buffer (pH 5.0–6.0), 0.1 M phosphate buffer (pH 7.0 and 8.0) or 0.1 M sodium carbonate buffer (pH 9.0 and 10.0). The ability for growth under anaerobic conditions was tested in R2A medium with or without 0.1 % (w/v) NaNO 3 [36]. To investigate the tolerance to NaCl, R2A broth was prepared in which sodium chloride concentrations was omitted (0 %) or added at 0.5–5.0 % (w/v, at intervals of 0.5 %) final concentration.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…The pH range for growth was determined (pH 5.0, 6.0, 7.0, 8.0, 9.0, 10.0) and using R2A media adjusted by appropriate buffering agents 0.1 M sodium acetate buffer (pH 5.0–6.0), 0.1 M phosphate buffer (pH 7.0 and 8.0) or 0.1 M sodium carbonate buffer (pH 9.0 and 10.0). The ability for growth under anaerobic conditions was tested in R2A medium with or without 0.1 % (w/v) NaNO 3 [36]. To investigate the tolerance to NaCl, R2A broth was prepared in which sodium chloride concentrations was omitted (0 %) or added at 0.5–5.0 % (w/v, at intervals of 0.5 %) final concentration.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…The genus Hymenobacter encompassed 100 validly published species on LPSN (https://lpsn.dsmz.de/genus/hymenobacter) at the time of writing (December 2022) [2]. One hundred type strains of the genus Hymenobacter have been isolated from various samples including air, freshwater, freshwater sediment, glaciers, lichen, marine sediment, plant, sand, seawater, and soil collected in tropical to polar regions, wastewater and meat, implying that members of the genus Hymenobacter are successful colonisers in a wide range of environmental conditions (Table S1) [1, 3–84]. Type strains of the genus Hymenobacter are characterized as aerobic, rod-shaped, red-pink or pink-pigmented, Gram-stain-negative, and heterotrophic [6, 13, 20, 30].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Hymenobacter species frequently exhibit resistance to UV, cold temperatures and heavy metals. So far, a few Hymenobacter species have been obtained from plant tissues, including the bark of Ginkgo biloba [21], dry spikelet clusters of grass Setaria viridis [22] and Antarctic lichen [23]. In our previous study, Hymenobacter was found to be one of the dominant taxa in the microbial community of wheat leaves [24].…”
Section: Introductionmentioning
confidence: 99%